Perceptions of Online Teacher Feedback Via Screencast among Indonesian Studentsin Online Writing Classes - Sari, Ratih Novita; Cahyono, Bambang Yudi (JOLLT Journal of Languages and Language Teaching, 2024)
There have been several studies interested in combining Internet Computer Technology (ICT) in writing because it improves the writing performance of L2 students in a widespread link to instruction. However, an earlier study has concentrated on the specific writing technologies employed. Few research has examined students’ impressions of Screencast’s use as an online video-audio tool for delivering feedback. This study adds to the corpus of knowledge about Indonesian students’ perspectives on feedback. Participation, revision incorporation, feedback performance, and student preferences are the four feedback components examined in this research. The acquisition of primary data used varied methods. Online perception surveys were sent to Indonesian second-year college students. Personal and quasi interviews were also employed to improve data and learn what may drive students to perceive more. To analyse the interview data, a descriptive analysis was performed. Students reported a high level of pleasure while using video feedback with a particular technology, Screencast, in an online writing course. The interview data provide support. The students believed that video feedback allows them to strengthen their writing skills more effectively than textual feedback provided by the teacher. In this study, the implications for language teaching and learning practice are examined further.